2007
DOI: 10.1029/2006jd007992
|View full text |Cite
|
Sign up to set email alerts
|

Global source attribution of tropospheric ozone: Long‐range transport from various source regions

Abstract: We examine contributions from various source regions to global distributions and budgets of tropospheric ozone (O3) in the context of intercontinental transport, using tagged tracer simulation with a global chemical transport model. For tagging O3, we consider regional separation of the model domain on the basis of the distributions of O3 chemical production. We define 14 polluted source regions (14 tracers) in the boundary layer (North America, Europe, China, etc.) and 8 regions (8 tracers) in the free tropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
205
1
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 197 publications
(213 citation statements)
references
References 77 publications
(140 reference statements)
5
205
1
2
Order By: Relevance
“…In the tagged-tracer simulation used in this study, the concentration of ozone calculated by a stratospheric chemistry climate model was assimilated into CHASER above the tropopause. If we assimilated the ozone concentration only above 55 hPa (∼20 km) altitude as in Sudo and Akimoto (2007), stratospheric ozone input would be estimated to be about 560 Tg(O 3 ) year −1 , which well falls within the range shown in Stevenson et al (2006). However, comparisons between the calculated concentrations of ozone with the several ozonesonde observations revealed that the simulation limiting the assimilation of stratospheric ozone above 55 hPa obviously overestimated the concentration of ozone, particularly at the upper troposphere.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…In the tagged-tracer simulation used in this study, the concentration of ozone calculated by a stratospheric chemistry climate model was assimilated into CHASER above the tropopause. If we assimilated the ozone concentration only above 55 hPa (∼20 km) altitude as in Sudo and Akimoto (2007), stratospheric ozone input would be estimated to be about 560 Tg(O 3 ) year −1 , which well falls within the range shown in Stevenson et al (2006). However, comparisons between the calculated concentrations of ozone with the several ozonesonde observations revealed that the simulation limiting the assimilation of stratospheric ozone above 55 hPa obviously overestimated the concentration of ozone, particularly at the upper troposphere.…”
Section: Discussionmentioning
confidence: 55%
“…Stevenson et al (2006) summarized the stratospheretroposphere exchange (STE) of ozone calculated from 26 atmospheric chemistry models, and showed that there is a large variety in estimates for stratospheric ozone input fluxes ranging from 296 to 930 Tg(O 3 ) year −1 (see Table 5 in Stevenson et al (2006)). In their intercomparison and also in the analysis in Sudo and Akimoto (2007), CHASER was reported to give a value for stratospheric ozone input of about 500 Tg(O 3 ) year −1 . In the tagged-tracer simulation with CHASER used in this paper (Nagashima et al 2010), the stratospheric ozone input is estimated to be about 135 Tg(O 3 ) year −1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations